Hope and mealtime insulin boluses are associated with depressive symptoms and glycemic control in youth with type 1 diabetes mellitus. Issue 7 (5th June 2018) - Calkins‐Smith, Alison K; Marker, Arwen M; Clements, Mark A; Patton, Susana R
Abstract : Adherence to treatment regimen is associated with improved glycemic control and is particularly problematic during adolescence for those with type 1 diabetes mellitus (T1DM). Both glycemic control and adherence may be negatively impacted by poor psychological outcomes in adolescence, such as depressive symptoms and low hopefulness. The purpose of this study was to examine associations between the mealtime insulin bolus score (BOLUS), a more robust proxy measure of adherence than frequency of blood glucose monitoring or self‐report, with depressive symptoms, hope, and hemoglobin A1c (HbA1c). Ninety adolescents completed measures of hope (Children's Hope Scale) and depressive symptoms (Center for Epidemiologic Studies—Depression Scale), as well as lab‐based measures of HbA1c and mealtime insulin bolus scores (BOLUS). Higher levels of hope were associated with lower levels of depressive symptoms, more frequent mealtime insulin boluses, and better glycemic control. Higher levels of BOLUS behavior were associated with lower depressive symptoms and better glycemic control. Both BOLUS behavior and hope independently and significantly impacted the relationship between depressive symptoms and HbA1c, suggesting a possible mediation. Since hope and BOLUS were each associated with the relationship between depressive symptoms and glycemic control, following confirmation of this relationship in a longitudinal study, clinics may consider measuring hope and BOLUS among youth with high depressive symptoms and further investigating BOLUS behavior and hope as potential intervention targets to improve glycemic control.